Analisis Fitokimia Air Rebusan Daun Mantalalu (Euphorbia hirta L) Asal Kota Palu Provinsi Sulawesi Tengah: Phytochemical Analysis of Mantalalu Leaves Boiled Water from Palu City Central Sulawesi - Asniati; Muthmainnah (KOVALEN: Jurnal Riset Kimia, 2021)
One of the herbal plants that have long been used as traditional herbal medicine by Central Sulawesi peoples is Mantalalu (Euphorbia hirta L). Central Sulawesi peoples used this Mantalalu to appendicitis medicine. The chemical compound contained in Mantalalu plant has a role in providing different pharmacology. A study was conducted about the chemical compound content Mantalalu plant (Euphorbia hirta L). The method of this research was boiling dried leave and wet leave of Mantalalu plant and phytochemical test including flavonoids tests, alkaloids tests, saponins tests, polyphenol, and tannin tests. The results of this research showed that the decoction of dried and wet leaf samples of Mantalalu plant contained flavonoid, polyphenol, tannin, and saponins bioactive compounds.